AUDIO VISUAL MEDIA DESIGN FOR PRACTICAL MICROBIOLOGY LEARNING - Aryeni Aryeni; Endang Sulistyarini Gultom; Qisthy Adha Fajriati; Nila Zusmita Wasni (Jurnal Pelita Pendidikan, 2023)
This study aims to describe the process of making audio-visual media and to determine the feasibility of it based on the assessment of material experts, media experts and student responses. This research is a descriptive study that adopts the ADDIE development step which has five stages. However, this research is limited to only three stages, the analysis, design, and development stages. The population used in this study were all majoring students of Biology in the 2018 at Unimed and the sample of this study were 40 majoring students of Biology in the 2018 who had taken microbiology courses at Unimed. Theinstrument used in this study was a questionnaire using a Likert scale. The results showed that videos of sterilization and media making, videos of observing bacterial colonies and counting the number of bacteria using the pour plate dilution method, isolation videos of pure bacteria cultures, videos of bacterial staining, videos of bacterial biochemical activity, and video of testing of antibacterial activity on sponge symbionts against bacteria MDR (Multi Drug Resistance) is categorized as very feasible based on the assessment of material experts, media experts and student responses.